CLASSIC MEDIA TRANSFORMATION PROCESSES AND ORIGIN OF NEW MEDIA SYSTEM SEGMENT IN EUROPE - J. O. Moskvina (Модернизация, инновация, развитие, 2016)
Mobile revolution took place at the beginning of XXI century resulting from which the mass media (MM) as mass communication means has first acquired an addition in the form of mobile Internet and then transformed into a new branch – mobile media. All that has changed the whole face of journalism. Classic forms of the profession have also actively transformed. A mobile journalism got born that made it possible for any person to participate on-line in creation of socially relevant information. Using the mobile technology, ordinary citizens have created an alternative to usual MM sample of the XX century, some new media empire. Usual MM (press, radio, television) where active interaction between information manufacturers and the audience is excluded were forced to change under pressure of new technologies and demands of the audience. Following the demand trends, Internet, initially stationary and then mobile, has emerged as global infrastructure of interactive communication.